The world revolution of westernization : the twentieth century in global perspective - Von Laue, Theodore H. 1916-2000 (Oxford Univ. Press, 1987)
Theodore H. von Laue: The World Revolution of Westernization. The Twentieth Century in Global Perspective. Oxford University Press, New York-Oxford 1987. 396 Seiten, 24,95 Dollar